Factors influencing optical uniformity of YAG single-crystal fiber grown by micro-pulling-down technology. Issue 45 (29th October 2019) - Wu, Baiyi; Nie, Hongkun; Wang, Anye; Zhang, Jian; Jia, Zhitai; Zhang, Baitao; Fu, Xiuwei; Hu, Qiangqiang; He, Jingliang; Tao, Xutang
Abstract : This work reports on the growth of Nd:YAG single crystal fibers by the micro-pulling down (μ-PD) method, and factors of optical uniformity and laser operation have been discussed. Abstract : Single-crystal fiber (SCF) combines the advantages of bulk crystal and glass fiber gain media and shows broad application prospects in all-solid-state lasers. In this work, high-quality crack-free Nd:YAG SCFs with diameters of 0.8–1 mm were successfully grown by the micro-pulling-down (μ-PD) method. The as-grown SCFs showed homogeneous Nd 3+ distribution, with a diameter fluctuation of less than 5%. The X-ray Laue patterns on the different crystal positions also revealed good crystalline consistency. Moreover, the core stress problems were investigated in terms of growth orientation to improve the crystal quality, and seed crystals with orientation of <111>, <100> and <100> to <110> 15° were used for crystal growth. Continuous-wave laser operations at 1064 nm were realized with the as-grown Nd:YAG SCFs. The maximum output of 8.32 W with a laser beam quality factor M 2 = 1.08 was achieved.